Peran Guru Bimbingan Konseling Dalam Melaksanakan Manajemen Bimbingan Konseling - Fatahillah, Ahmad (Science and Education Journal (SICEDU), 2024)
Implementing educational programs that aim to make the nation's life more intelligent and create a competent generation is the responsibility of an educator. A counselor, specifically a guidance and counseling teacher, must have good management (management and regulation) in order to have good steps in implementing the program that will be created. Management that is managed and implemented well will achieve the goals desired by the supervising teacher. Teachers who work with good management are supervising teachers who have a program and implement the program according to the needs of the school's students.